2016
DOI: 10.1037/xge0000229
|View full text |Cite
|
Sign up to set email alerts
|

Action versus state orientation moderates the impact of executive functioning on real-life self-control.

Abstract: Self-control is commonly assumed to depend on executive functions (EFs). However, it is unclear whether real-life self-control failures result from deficient EF competencies or rather reflect insufficient conflict-induced mobilization of executive control, and whether self-control depends more critically on function-specific EF competencies or general executive functioning (GEF), that is, common competencies that underlie all EFs. Here we investigated whether failure-related action versus state orientation, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 112 publications
9
66
0
Order By: Relevance
“…The magnitudes of the correlations between the six inhibitory control tasks were generally low (.29 or smaller), but are consistent with the results of previous studies and seem not to be restricted to college samples, but also present in samples with a wider age range and across different levels of intellectual abilities (Cheung et al, 2004;Enge et al, 2014;Enticott et al, 2006;Friedman & Miyake, 2004;Miyake et al, 2000;Shilling, Chetwynd, & Rabbitt, 2002;Singh et al, 2018;Wolff et al, 2016). This is why we applied a latent variable analysis:…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The magnitudes of the correlations between the six inhibitory control tasks were generally low (.29 or smaller), but are consistent with the results of previous studies and seem not to be restricted to college samples, but also present in samples with a wider age range and across different levels of intellectual abilities (Cheung et al, 2004;Enge et al, 2014;Enticott et al, 2006;Friedman & Miyake, 2004;Miyake et al, 2000;Shilling, Chetwynd, & Rabbitt, 2002;Singh et al, 2018;Wolff et al, 2016). This is why we applied a latent variable analysis:…”
Section: Discussionsupporting
confidence: 87%
“…Enge et al, 2014). Therefore, we combined error rates and reaction times into inverse efficiency scores (IES; Bruyer & Brysbaert, 2011;Townsend & Ashby, 1983), as was done in a previous study that applied a latent variable approach on executive function tasks (Wolff et al, 2016). Specifically, we expected higher correlations and a better fit for estimated models with the IES compared to the standard outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of effectively reducing negative affect by mobilizing control, thus addressing the conflict itself and solving it in accordance with superordinate goals, individuals with low self-control may use less conflictcentered emotion regulation strategies or even ruminate about the emotion itself. In line with this conjecture, in a recent study (Wolff et al, 2016) we found that high executive control competencies predicted lower proneness to daily SCFs in individuals with a disposition toward Baction orientation^(who have been shown to efficiently recruit control in response to conflict; Goschke & Bolte, 2018;Kuhl & Beckmann, 1994), but not in Bstate-oriented^individuals, who tend to respond to conflicts with rumination rather than enhanced control recruitment (Fischer, Plessow, Dreisbach, & Goschke, 2015;Jostmann & Koole, 2007).…”
Section: Discussionsupporting
confidence: 63%
“…During task battery performance, subjects were alone in a quiet room and allowed to do self-paced breaks between the individual tasks. The tasks included the number Stroop task (Stroop, 1932) to measure inhibition (using a mouse-click version in contrast to common keyboard-based response), the emotional face approach-avoidance task (Face-AAT; Heuer, Rinck, & Becker, 2007) to investigate reactions to emotional faces, the AX continuous performance task (AX-CP; Cohen, Barch, Carter, & Servan-Schreiber, 1999) to measure context processing, goal maintenance and updating, a novel variant of an intertemporal choice task (ITC, Scherbaum, Dshemuchadse, Leiberg, & Goschke, 2013) to measure individually determined advantageous and disadvantageous choices, and a go-nogo task (Wolff et al, 2016) to measure inhibition.…”
Section: Behavioral Tests and Tasksmentioning
confidence: 99%